2019
DOI: 10.1002/bjs.11024
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis of a multicentre randomized clinical trial comparing surgery with conservative management for recurrent and ongoing diverticulitis (DIRECT trial)

Abstract: Background:The results of the DIRECT trial, an RCT comparing conservative management with elective sigmoid resection in patients with recurrent diverticulitis or persistent complaints, showed that elective sigmoid resection leads to higher quality of life. The aim of this study is to determine the cost-effectiveness of surgical treatment at 1-and 5-year follow-up from a societal perspective. Methods: Clinical effectiveness and resource use were derived from the DIRECT trial. The actual resource use and quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 23 publications
0
14
0
4
Order By: Relevance
“…To slightly elaborate on the costs, an FDG-PET/CT costs €1200 on average 24 and an SL costs €900 on average, based on the minute price of the operating room (including operating room, nurses, surgeon, anesthesiologist, overheads). 25 However, we await the results of the PLASTIC study in order to make statements on the economic aspects.…”
Section: Discussionmentioning
confidence: 99%
“…To slightly elaborate on the costs, an FDG-PET/CT costs €1200 on average 24 and an SL costs €900 on average, based on the minute price of the operating room (including operating room, nurses, surgeon, anesthesiologist, overheads). 25 However, we await the results of the PLASTIC study in order to make statements on the economic aspects.…”
Section: Discussionmentioning
confidence: 99%
“…Risk for stoma was 5%–21%, and severe complication requiring reoperation occurred in 10%–28% patients randomized to surgery arm ( 70 , 71 ). From an economical point of view and based on DIRECT trial data, elective sigmoid resection was also found to be cost-effective ( 74 ). Some limitations of the trials are worth mentioning.…”
Section: Diagnosticsmentioning
confidence: 99%
“…The authors found a significant improvement in gastrointestinal quality of life in the resection group, and reported that a quarter of the patients in the conservative management group ended up opting for a resection by 6 months and nearly half at 5 years. Additionally, at 5 years, these improvements in quality of life may persist, and the elective resection approach may also be more cost effective [ 65 , 66 ]. A similar, more recent publication, the LASER trial of Finnish patients, published essentially identical findings from their own RCT [ 67 ].…”
Section: Management Of Complicated Diverticulitismentioning
confidence: 99%